"Walking ATMs": Street Criminals' Perception and Targeting of Undocumented Immigrants. (2nd January 2023) - Caraballo, Krystlelynn; Topalli, Volkan
Abstract: Research suggests undocumented immigrants are vulnerable to robbery, burglary, and car theft, but studies have focused exclusively on victims' perspectives rather than those of street offenders. This study draws from in-depth, semi-structured interviews of 25 active street offenders from a major southeastern US city to understand offenders' perspectives and motivations for deciding whether to target immigrants. Our findings support that some street offenders explicitly select targets based on perceived individual and socio-structural risk factors and the assumption of undocumented status. These include objective and subjective assessments of immigrants' reliance on cash-intensive employment, fear of deportation, and inability to access formal justice systems. Our interviews with offenders reveal they and their acquaintances rely on mainstream stereotypes of immigrants (documented and undocumented) and of Latinx populations to determine vulnerability, select targets, and to a lesser extent, justify victimization. Our results highlight the unintended consequences of US immigration policies on crime against immigrants.